The Methodological proposal as an alternative for the integration of knowledge - Aguilar Gordón, Floralba del Rocío (2020)
This article reflects on the methodological proposal as an alternative of qualification, as a strategy for solving problems and as a way of integrating knowledge that enables the integral formation of human beings; in this sense, this document explains the stages of its constitution and analyses its characteristics, contributions and structure. This paper aims to establish a set of guidelines for the structuring of a critical, creative and innovative methodological proposal that responds to the emerging needs of the educational reality and of the society in general. The methodological proposal becomes a pedagogical and didactic strategy that enhances different skills and competences in the human being; it is a reference for professional training that values the research processes, the analytical, critical and reflective perception of the facts, phenomena and educational-contextual situations in which the subjects are immersed. In the daily work of the professor predominates the uncertainty about the processes that should be followed in order for the student to apply the acquired knowledge; hence the content in this manuscript can be an opportunity and an action to be carried out so that the student can practice the acquired theoretical corpus. The manuscript uses the phenomenological-hermeneutic method that allows a direct approach to the object of study and promotes the understanding of the individuals in their context.